Biochemical changes in the serum of pregnant women in the thirdtrimester - Ahmed Salih, Nadia (Tikrit Journal of Pharmaceutical Sciences, 2023)
The current study was designed to verify the implication of pregnancy in the induction of serum lipid and lipoprotein changes in pregnant women . To achicve this aim ,50 pregnants and 50 age matched healthy non pregnant women {control group) were enrolled. Serum Iron, Hb, cholesterol . TIBC triglyceride, HDL — cholesterol . LDL- cholesterol ,VLDL- triglyceride concentration were measured in all subjects. Significant (P<0.0) increases were found in the levels of serum TIBC, cholesterol, triglyceride. LDL and VLDL in the pregnant women of third trimesters when compared with those of the control group. HDL levels were found to be significantly (P<0.0) elevated in pergnants of the third trimesters with those of the control group. Significant (P<0.0) decreases were found in the levels of serum iron and Hb in the pregnant women when compared with control group.